THE TORT LIABILITY IN PORTUGAL: THE FAULT REQUIREMENT – THE PARTICULAR CASE OF PUBLIC SCHOOLS - Jorge Barros Mendes (European Scientific Journal, ESJ, 2014)
The Law 67/2007 of December 31st has changed the arrangements liability of the state bringing numerous innovations in the Portuguese legal system over the past diploma. We will analyze synthetically, one of the requirements for the Portuguese state will be sentenced - the concept of fault. This concept appears now clearly enshrined in Portuguese administrative law, contrary to the previous regime which referred to the civil law and the concept of bonus pater familiae. We will try to understand it with the Law of The Tort Liability of the State and trying to understand if we have in portugal the objectification or subjectivation of the fault. We will conduct a review of certain decisions of the Portuguese courts on this matter, essentially trying to understand how the courts decided under the previous law and decide how to the present law.